2013
DOI: 10.5665/sleep.2538
|View full text |Cite
|
Sign up to set email alerts
|

Children's Sleep Needs: Is There Sufficient Evidence to Recommend Optimal Sleep for Children?

Abstract: It is widely recognized that sleep is important for children's health and well-being and that short sleep duration is associated with a wide range of negative health outcomes. Recently, there has been much interest in whether or not there are sufficient data to support the specific recommendations made for how much sleep children need. In this article we explore concepts related to children's sleep need, discuss the theory, rationale, and empirical evidence for contemporary sleep recommendations, and outline f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(119 citation statements)
references
References 64 publications
5
111
0
3
Order By: Relevance
“…Our study further confirmed the high prevalence of sleep deprivation and irregular sleep patterns among adolescents in Hong Kong, especially compared with white adolescents. 2,3,11 In agreement with previous studies, [23][24][25][26][27]29,30 there was a prominent enhancement of sleep knowledge among adolescents in the intervention group, with a medium effect size. The marked increase in sleep knowledge, however, did not translate into a change in sleep behavior.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Our study further confirmed the high prevalence of sleep deprivation and irregular sleep patterns among adolescents in Hong Kong, especially compared with white adolescents. 2,3,11 In agreement with previous studies, [23][24][25][26][27]29,30 there was a prominent enhancement of sleep knowledge among adolescents in the intervention group, with a medium effect size. The marked increase in sleep knowledge, however, did not translate into a change in sleep behavior.…”
Section: Discussionsupporting
confidence: 80%
“…1,2 Nonetheless, consistent data suggest a crosscultural difference at which Asian adolescents obtained much less sleep (∼1 hour) than their European and US counterparts. 2,3 Compensation of sleep debt during weekends with .2 hours of discrepancy was often documented among young students.…”
Section: What This Study Addsmentioning
confidence: 82%
See 1 more Smart Citation
“…There is a clear need for sleep restriction/extension interventions in children and youth that try to determine upper and lower limits of healthy sleep duration (i.e., dose-response curve). Although current sleep recommendations tend to suggest that a generalized optimum exists for the population, it is possible that different optimal sleep durations exist for different health outcomes (Matricciani et al 2013). There is also inter-individual variability in sleep needs (e.g., because of genetic differences or sociocultural contexts) and sleeping longer or shorter than the recommended times may not necessarily mean that it will adversely affect health.…”
Section: No Serious Imprecisionmentioning
confidence: 99%
“…The National Sleep Foundation recommends sleeping between 9-11 h/night for school-aged children (ages 6-13 years) and 8-10 h/night for adolescents (ages 14-17 years) to maximize overall health and well-being (Hirshkowitz et al 2015). Although the ideal amount of sleep per night varies from one person to another, sleep duration recommendations play an important role in informing public policies, guidelines, interventions, and parents and children/youth of healthy sleep behaviours (Matricciani et al 2012b(Matricciani et al , 2013.…”
Section: Introductionmentioning
confidence: 99%